An investigation over microstructure and HIP processing effects on wear performance of pure chromium parts fabricated by laser powder bed fusion - Bulutsuz, Asli Gunay; Gulec, Buse; Gokcekaya, Ozkan; Gardstam, Johannes; Nakano, Takayoshi; Yilmazer, Hakan (ELSEVIER SCI LTD, 2024)
Chromium (Cr) and its alloys have long been valued for their exceptional properties, including corrosion resistance and high-temperature stability, rendering them indispensable in industrial applications such as chemical processing, energy production, and aerospace. However, due to the difficulties in Cr-based alloy manufacturing, there is a need for novel manufacturing methodologies. Additive Manufacturing (AM) emerges as a promising approach, particularly Laser Powder Bed Fusion (LPBF), which allows for intricate designs, reduced material waste, and simplified assembly. However, certain issues still need to be addressed, including defects like cracks and porosities in the manufactured parts. Post-processing techniques such as Hot Isostatic Pressing (HIP) have gained prominence for enhancing the material properties and quality of AM parts, including those produced using LPBF. HIP treatments are effective in eliminating internal pores, although some challenges remain, notably the presence of trapped argon and grain coarsening side effects of HIP process parameters. This study focuses on LPBF-processed pure chromium parts with crystallographic texture and investigates their properties after HIP treatment, including microstructure, hardness, and tribological performance. According to the obtained results: the HIP process reduced cracks, especially in the center region, but increased gaps in the side region. HIP also hindered grain realignment, limiting grain growth, and resulting in high HAGB density and low MUD values. Elevated HIP processing pressure negatively affected tribological performance due to increased grain size, and reduced hardness. This study, for the first time, realized the effect of HIP conditions on the microstructure and tribological performance of LPBF-processed pure Cr.
Keywords: Laser powder bed fusion; Pure Cr; Crystallographic texture; Hot isostatic pressing; Wear performance; TRIBOLOGICAL PROPERTIES; COATINGS; BEHAVIOR; DENSIFICATION; PARAMETERS; DENSITY; ALLOYS; Materials Science; Metallurgy & Metallurgical Engineering